Pembuatan Sarabba Susu Sapi sebagai produk unggulan Desa Cendana - Muhammad Alfaridzi Fahrurrozy; Azizah Aulia Ammar; Nur Arfima Arifin; Andi Mentari; Ernawati M Tika B; Putri Azzahra; Raisul Amin R; Ahmad Azhary; Anisah Putri; Munawir Gasali; Suherman (Jurnal Dedikasi Masyarakat, 2021)
Desa Cendana in the Cendana District, Enrekang Regency, holds significant potential in the dairy cattle sector, with the largest population of cattle in the region, totaling 3,402 head, and a daily milk production of 482 liters. However, dairy products such as Dangke and milk crackers are still underutilized, resulting in suboptimal economic benefits for the community. To enhance economic value and diversify dairy products, Sarabba Susu Sapi has been developed as a flagship product. Sarabba is a traditional drink from South Sulawesi, typically made from ginger, palm sugar, and coconut milk. In this innovation, cow's milk replaces coconut milk to add value and provide better health benefits. The primary objective of this initiative is to increase community income through the diversification of dairy-based products and to introduce Sarabba Susu Sapi as a flagship product of Desa Cendana. The methods employed include socialization and training for the community on the preparation and benefits of Sarabba Susu Sapi. This socialization involves product preparation demonstrations and education on health benefits. The results of this initiative indicate that Sarabba Susu Sapi has been well received by the community and holds promising market potential. Through effective socialization, Sarabba Susu Sapi has the potential to create new job opportunities and to become a flagship product that strengthens the cultural and economic identity of Desa Cendana.